Penguatan Kesadaran Remaja mengenai Dampak Pernikahan Dini terhadap Kesehatan Reproduksi - Windy Dermawan; Ivan Darmawan; Mustabsyirotul Ummah (Jurnal SOLMA, 2021)
Background: The rate of early marriage in Indonesia is the second highest in ASEAN. In fact, according to UNICEF, the highest adoption of early marriage in Indonesia occurred in West Java Province. One of the impacts of early marriage is the increased vulnerability to reproductive health threats in society, especially for adolescents who are in the stage of development of their reproductive organs. This is neglected by society even though reproductive health has a major effect on human survival, both in the aspects of regeneration, economy, and socio-culture. This paper aims to determine the results of strengthening adolescent awareness about early marriage and its impact on reproductive health. Method: Used to solve problems is focused group discussion on identifying and formulating activity problems, providing understanding through socialization activities and stopping early marriage campaigns in the form of posters, and evaluation activities. Problem Based Learning and Community Based Research (CBR) are used to involve the subject of activities in solving problems and formulating ideas for solving problems together. Result: This activity found that there was an increase in the cognitive, affective and psychomotor aspects of activity participants by 75% regarding the impact of early marriage on reproductive health. Conclusion: This activity is able to contribute to the development of aspects of perceptions, attitudes and actions of the participants in supporting the strengthening of youth awareness about early marriage and reproductive health.